Teaching adult second language learners - McKay, Heather, 1950-; Tom, Abigail, 1941- (Cambridge ; New York : Cambridge University Press, 1999)
"Teaching Adult Second Language Learners addresses the special needs of adults studying English, particularly those who have immigrated to English-speaking countries. It provides a useful summary of the principles involved in teaching adults as well as a wealth of activities specially designed for adult learners." "The book is divided into three sections: section I contains an introduction to the adult language learner. It also discusses assessment and placement of students, and the organization of courses and lesson organization; section II gives teachers techniques for building community in the classroom; section III provides activities designed for students at various levels that are organized thematically around topics such as self-identification, food, clothing, and work. Whenever possible, alternative activities are suggested to accommodate the needs of multilevel classes."--Jacket.
Includes bibliographical references (p. 231-232) and indexes.
Keywords: Language and languages -- Study and teaching; Second language acquisition; Adult education